2015
DOI: 10.20999/nam.2015.b007
|View full text |Cite
|
Sign up to set email alerts
|

Criminal and Economic Activity in Mexico

Abstract: En este artículo se examina la relación entre actos violentos o delictivos y la actividad económica en México. El ejercicio se lleva a cabo dentro del marco de la econometría de series de tiempo. Por medio de la estimación de ecuaciones de cointegración y ciclo común se evalúa si las series comparten una tendencia y si responden de manera similar a choques transitorios. Los resultados indican que, en el largo plazo, la actividad económica cointegra, con tres medidas de inseguridad, homicidios, secuestros y rob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Finally, it is concluded that corruption and homicides over time have adverse effects on the development of the economy, since productivity, investment, capital, economic growth and development decrease [42]. This is supported by Quiroz, Castillo, Ocenguera and Verela [43] by identifying a negative non-linear relationship between economic growth and insecurity measures such as: homicide, kidnapping and theft.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Finally, it is concluded that corruption and homicides over time have adverse effects on the development of the economy, since productivity, investment, capital, economic growth and development decrease [42]. This is supported by Quiroz, Castillo, Ocenguera and Verela [43] by identifying a negative non-linear relationship between economic growth and insecurity measures such as: homicide, kidnapping and theft.…”
Section: Literature Reviewmentioning
confidence: 83%
“…As a complement to the research that attributes the rise in violence indicators to factors associated with poverty, culture, the war between cartels (Quiroz-Felix et al, 2015), and even the emergence of new actors such as the national guard, the army or the navy, we start from the thesis that the main cause of the upturn in violence lies in the behavior of the political class, without thinking about the temporality of their position (they believe that they will always be part of the political class and therefore will enjoy immunity and impunity), nor about their margin of affectability (they consider themselves untouchable and that this immunity and impunity can be extended to their relatives), they approve policy measures (economic, labor, educational, energy, or legal) that have harmful consequences for society, mainly poverty, which creates a propitious ground to generate the problem we are dealing with: violence.…”
Section: ç Introductionmentioning
confidence: 99%